Intellectual property system and industrial development in Malaysia - Abdul Ghani Azmi, Ida Madieha; Gee, Lim Heng; Alavi, Rokiah (IIUM Press, 2009)
This work examines the economic impact of IP reforms in Malaysia. These reforms could be in two forms. The first is the introduction of specific economic and industrial policies to spur innovation and technological growth in certain sectors. The second is the reforms in the various intellectual property legislation either to encourage filing of application or to ease and expedite the examining and processing of IP filings. In quantifying the effect of IP reforms on FDI, IP creation and economic growth, the work adopts an established regression analysis model.